Rare Case Of Tenesmus In A Non-Descript Dog Due To A Penetrating Foreign Body (Applied Biological Research, 2014)
Tenesmus of gastrointestinal origin in dogs is usually accompanied by pain, cramping and  involuntary straining efforts. Tenesmus itself is not a disease and is a clinical symptom of colitis,  perianal fistulas, colonic and rectal tumours and even of diarrhoea in dogs (Kahn and Line, 2005).  This paper reportstenesmus in a non-descript dog due to a penetrating foreign body in rectal mucosa.
Keywords: Tenesmus; Foreign; Body